(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the 18 th century the general economic crisis in the Safavid state led to political decline. The pressure of the Shiite clergy under Shah Sultan Hussein aroused the outrage of the Sunni minority in the border regions, in particular, the Ghilzai Afghans in Kandahar, which ended in 1722 with their capture of the capital of the Safavid state, Isfahan. By this time, the central and eastern regions were in the hands of the Afghan tribes, the Caspian regions - in Tsarist Russia, and Azerbaijan, Shirvan and adjacent regions - in the Ottoman Empire. The Safavid prince Tahmasib, who fled from the besieged capital, declared himself the rightful ruler of Iran - Shah Tahmasib II (pr. 1722-1732). The revival of the national spirit began in 1726 when Nadir Quli Khan from the Turkic tribe Afshar joined the Takhmasib Shah. The army under the leadership of Nadir, by the end of 1729, having won a victory over the Afghans in three decisive battles, conquered Isfahan, in 1730 began the liberation of Azerbaijan from the Ottoman Turks and in 1732 - the Caspian regions from the Russian troops. By 1736, the territory of the Safavid state was completely cleared of foreign invaders.